Penerapan Konsep Manajemen Humas dalam Meningkatkan Reputasi Perusahaan di Indonesia: Studi Kasus pada Industri Telekomunikasi - Aulia, Ghea Ratu; Romlatun, Romlatun; Setiyadi, Bradley (Universitas Batanghari Jambi, 2025)
This research aims to explore how public relations (PR) practices can improve public perception of companies, especially in the telecommunications industry. Intense competition, the importance of open communication, responsiveness to public issues, and active engagement with stakeholders are recognized as the main factors that shape public opinion. The case analysis in this research explores successful public relations practices implemented by key companies in the telecommunications industry in Indonesia. The results of this research show that honest and open communication with customers, regulators and the public is the key to building trust and a solid reputation. Responsiveness to emerging issues is also considered an effective strategy for overcoming challenges and maintaining a good corporate image. This research also emphasizes the importance of crisis management as an integral part of effective public relations practice. Rapid change, a company's ability to respond quickly and effectively to a crisis can have a significant impact on a company's reputation.